An Evaluation of the Transdiagnostic Cognitive-behavioural Model of Eating Disorders - Lampard, Amy; Tasca, G.; Balfour, L.; Bissada, H. (John Wiley & Sons Ltd., 2013)
ObjectiveTo determine if the relationships between additional maintaining factors and core eating disorder maintaining mechanisms outlined in the cognitive-behavioural model of eating disorders are transdiagnostic.MethodPatients (n?=?1451) diagnosed with anorexia nervosa, bulimia nervosa (BN) or eating disorder not otherwise specified completed the Eating Disorder Examination Questionnaire, Eating Disorder Inventory-2 and Personality Assessment Inventory prior to entering treatment.ResultsMulti-group structural equation modelling results suggested that low self-esteem, overevaluation of weight and shape, and mood intolerance processes were transdiagnostic. However, some differences between diagnostic groups were observed. Dietary restraint was only positively associated with binge eating in BN, interpersonal difficulties were only associated with dietary restraint in eating disorder not otherwise specified and perfectionism was not associated with core eating disorder maintaining mechanisms in BN.DiscussionA mixture of transdiagnostic and disorder-specific processes was implicated in the maintenance of eating disorders, although longitudinal research is needed to validate results.